Nutrition Status of High Performance Rowers, Canoeists and Kayakers - Marius Baranauskas; Linas Tubelis; Rimantas Stukas; Edmundas Švedas; Laimutė Samsonienė; Diana Karanauskienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Rowing and canoeing-kayaking are some of the leading sports in Lithuania, and  athletes  have  achieved  victories  in  European  and  world  championships.  In  order  to  effectively  manage  the preparation of Lithuanian elite rowers, canoeists and kayakers, research in their nutrition status is important, relevant and necessary. Hypothesis: dietary intake of rowers and canoeists-kayakers comply with nutrition requirements. Research  aim  was  to  assess  nutrition  status,  physical  development  and  the  interactions  between  them  for Lithuanian Olympic team rowers, canoeists and kayakers. Research methods. Research on the nutrition status and supplementation was carried out in the preparatory competition  period  in  2012. The  sample  included  18.2  ±  2.3-year-old  rowers  (n  =  24)  and  21.5  ±  5.2-year-old canoeists-kayakers (n = 12). Body composition analysis and physical development of athletes was performed using multi-frequency bioelectrical impedance analysis (BIA) method. Research results. Regardless of gender, MFMI of kayakers-canoeists and rowers was only average. Athletes' dietary energy intake (EI) does not fully cover the energy expenditure, the diet lacks carbohydrates, dietary fibres, omega-3 fatty acids, vitamin D, and there is too much fat, saturated fatty acids and cholesterol. 92% of athletes take supplements. Most often athletes' dietary supplementation includes carbohydrates (73.9%), amino acids (73.9%), minerals (73.9%), vitamins (65.2%), and multivitamins (65.2%).   Discussion and conclusions. Nutrition status and physical development of Lithuanian elite kayakers-canoeists and rowers does not meet the requirements of nutrition. Diets of high performance kayakers-canoeists and rowers must be optimized, adjusted and individualized. Keywords: rowers, canoeists and kayakers, high sports performance, athlete nutrition.